Determinant factors of bank customers' demand for liquidity - Bernardo, C. D. (2015)
In contexts of economic instability investors show an increase in aversion to risk and prefer high liquidity and low-risk financial products. In this paper, we study the reasons behind bank customers holding wealth in the form of immediate liquidity. Using micro data on clients’ portfolios of a Portuguese bank, we ask whether there is a relationship between the bank’s capital ratio and the proportion of wealth that clients allocate to demand deposits, which is a relatively unexplored topic in the literature. Special attention is also paid to the impact of investors' financial knowledge by looking at professional group and age. Results indicate that when banks’ capital ratio decreases, savers put a larger fraction of their investment into demand deposits, especially savers with greater risk aversion and knowledge. Finally, we find evidence of an “age effect” and also that investors belonging to professional groups with more skills follow more sophisticated investment strategies.